Metal concentration in plant tissues of Ricinus communis L. (Castor oil) grown in soil contaminated with spent lubricating oil - DE Vwioko; GO Anoliefo; SD Fashemi (Journal of Applied Sciences and Environmental Management, 2006)
Castor oil plant seeds (Ricinus communis L.) were grown in spent lubricating oil (SLO) contaminated soil at concentrations of 1-6% (w/w, oil/soil). Plant height and stem girth were depressed by spent lubricating oil at concentrations of 2% (w/w) and above. One percent (1%) spent lubricating oil in soil promoted growth of plants when compared with control. Fresh and dry weights of R. communis plants grown in 1% oil treatment were significantly more than that of control. Spent lubricating oil in soil depressed pH. From the values obtained for metal concentrations in leaves, stems and roots, the concentrations of manganese and nickel were highest in the leaves. At 2% SLO and above, lead concentration was highest in the leaves too. Accumulation of the metals by plant parts were not concentration dependent. Specifically metal accumulation in R. communis, in the present study showed that Mn , Ni and Pb were mostly accumulated in the leaves; while V was highest in roots. Journal of Applied Sciences and Environmental Management Vol. 10(3) 2006: 127-134